2(x+8)-5(x+2)=-2(x+13)

Simple and best practice solution for 2(x+8)-5(x+2)=-2(x+13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+8)-5(x+2)=-2(x+13) equation:



2(x+8)-5(x+2)=-2(x+13)
We move all terms to the left:
2(x+8)-5(x+2)-(-2(x+13))=0
We multiply parentheses
2x-5x-(-2(x+13))+16-10=0
We calculate terms in parentheses: -(-2(x+13)), so:
-2(x+13)
We multiply parentheses
-2x-26
Back to the equation:
-(-2x-26)
We add all the numbers together, and all the variables
-3x-(-2x-26)+6=0
We get rid of parentheses
-3x+2x+26+6=0
We add all the numbers together, and all the variables
-1x+32=0
We move all terms containing x to the left, all other terms to the right
-x=-32
x=-32/-1
x=+32

See similar equations:

| 10-5c=-7c | | 7p+8=8p+p-8 | | q-1=2q-10 | | 9x-7=9(x-1)+17 | | 9-5c=-7c-9 | | (2x-5)^(2)-(x-6)^(2)=80 | | h=2h-10 | | -z+4=z-8 | | 3+9b=8b | | -7(x-4)=2x+23 | | 4(p+3)-2=18 | | 2(3c+5)=82 | | -3k+10=7k | | `5x-2=23` | | -d=-2d-10 | | 9(4+c)=99 | | (H+2)x25=5 | | -12=2z | | 11y-2=3y+14 | | 15g=30/g= | | 52x-48=28x | | 6-3a=-10 | | -11=r+3 | | 180=6x+15x+33 | | 71=9x-47 | | 4(1-3x)=2(-4x+7) | | 4z+12+-14=26 | | 2u–6=5u-78 | | 5u–78=2u–6 | | 3v+81=15v+9 | | 4z+12+-14=26z=2 | | 2x-5=44=5x |

Equations solver categories